Review of Current First-Line Pharmacotherapy Strategies for Thyroid Eye Disease - Ryniecka, Julia; Wojszczyk, Maciej; Zys, Damian; Pasek, Piotr; Kulbacka, Julia; Wójcikiewicz, Michalina; Chuncia-Ileczko, Marta; Kacperczyk, Julia; Arczewski, Filip; Dziedzic, Karol (Quality in Sport, 2025)
Thyroid eye disease (TED) is a challenging autoimmune disorder that often requires therapeutic intervention. Glucocorticoids (GCs), particularly in intravenous (IV) regimens, remain the first-line treatment due to their strong anti-inflammatory and immunosuppressive effects. This paper focuses on the efficacy, protocols, and safety profiles of selenium supplementation and glucocorticoid therapy, emphasizing its central role in TED management. Alternative therapies, such as teprotumumab, rituximab, and tocilizumab, are briefly discussed as potential options for patients with moderate-to-severe TED, who are unresponsive or intolerant to glucocorticoids. Adherence to recommended dosing protocols and careful monitoring of adverse effects are essential to optimize treatment outcomes.